Assessment of the Quality of Inpatient Meals and Nutrition and Dietetics Service Processes in Select Philippine Public Hospitals - Casas, Lyle Daryll D. (Archīum Ateneo, 2023)
Aims The nutrition and dietetics service in Philippine public hospitals was implemented by the Department of Health in 2016 to standardise the daily allowance and nutritional content of inpatient meals. Five years later, it is timely for the Department of Health to assess the quality of inpatient meals and mandated nutrition processes in areas such as staffing, food service, and outcomes monitoring. Methods A mixed-method sequential explanatory design was employed using (1) quantitative assessment through a facility survey (n = 193 hospitals) and (2) qualitative exploration of quantitative results through 6 focus group discussions (n = 36 hospitals). Results Philippine public hospitals were unequipped with the inputs necessary to implement processes that produce high-quality meals for patients. The hospitals were unable to comply with the required minimum meal allowance (51%), nutritional content of meals (40%), and food service standards. Moreover, they had insufficient human resources and inefficient food procurement practices. Conclusions: The quality of nutrition care and inpatient meals in Philippine public hospitals, who serve mostly people on low incomes, is a neglected problem in the Philippines. Moving forward, a systems approach involving the Department of Health, its regional offices, and hospital management is necessary to equip Philippine public hospitals with the inputs and structures necessary to provide high-quality nutrition care and inpatient meals that will facilitate patient recovery and overall patient health.